The ubiquitination–autophagy axis in cancer therapy resistance: mechanistic insights and therapeutic opportunities - Zhang, Hengrui; Yan, Hanxi; Liu, Yulin; Zeng, Anqi; Song, Linjiang (Frontiers in Pharmacology, 2026)
Therapy resistance is a major challenge in cancer treatment. Growing evidences reveal that the interaction between ubiquitination and autophagy plays a key role in regulating resistance to chemotherapy, radiotherapy, targeted therapy, and immunotherapy. In this review, we systematically summarize recent studies that reveal how specific E3 ligases, deubiquitinating enzymes, and ubiquitin-like modifiers influence autophagic flux and modulate the tumor response. We focus on key regulatory circuits—such as the Tripartite-motif protein 65–miR-138-5p–Autophagy related 7 (TRIM65–miR-138-5p–ATG7)pathway in non-small cell lung cancer, the Cullin-RING Ligase 4(CRL4)–mitophagy signaling pathway in ovarian cancer, and the Ubiquitin Specific Peptidase 14–S-phase kinase-associated protein 2(USP14–Skp2) axis in B-Raf proto-oncogene (BRAF) inhibitor resistance—illustrating the dual regulatory functions of ubiquitin-dependent protein turnover and autophagy. Furthermore, we highlight how noncoding RNAs and the tumor microenvironment influence ubiquitination-modulated autophagy and contribute to immune resistance or DNA repair remodeling. Finally, we discuss potential therapeutic strategies, including Proteolysis Targeting Chimeras (PROTACs), dual E3 ligase/autophagy inhibitors, and autophagy flux modulators, to overcome resistance and enhance treatment efficacy across multiple cancer types. These insights establish the foundation for targeting the ubiquitin–autophagy network as a cohesive strategy to combat refractory cancer.